“Mulher serve pra tudo...”?: O feminino nas vozes de mulheres de diferentes gerações - Gaudenci, Anna Giulia Coppe (Universidade Federal de São Carlos, 2022)
This work aims to understand the dynamics of interpersonal relationships experienced by women and other people from different family nuclei, and, thus, bring their views on their bodies and the female, from the transmission of knowledge between generations. It is intended to understand how the construction of gender identities from the family nuclei takes place, considering “gender” as a social and historical construction and of education for the female as a learning process. From this, the intention is to bring elements about the different origins and different traditions and cultures that women translate through memories. It is concluded from the research that the perceptible cultural changes from one generation to the other point to the possibility of establishing more democratic and egalitarian relationships between women. Therefore, the method used was the collection of oral reports, through semi-structured interviews, with 10 women belonging to three different family groups and from different generations: granddaughters, daughters, grandparents and great-grandparents.
“Women are for everything...”?: The feminine in the voices of women of different generations
Keywords: Gênero; Educação; Feminino; Relatos Orais; Gender; Education; Feminine; Oral reports; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM